Chalcopyrite Dissolution: Challenges - Bevilaqua, Denise [UNESP]; Toledo, Ailton Guilherme Rissoni [UNESP]; Crocco, Laíze Guimarães [UNESP]; Peres, Riberto Nunes [UNESP]; da Costa, Rachel Biancalana [UNESP]; Benedetti, Assis Vicente [UNESP]; Tuovinen, Olli H. (Springer Nature, 2024)
Chalcopyrite is the main source of copper in the world, amounting to nearly 70% of the copper reserves. Nonetheless, chalcopyrite is highly recalcitrant to chemical and biological processing for copper extraction. Concentration by flotation and Cu recovery by pyrometallurgical techniques are still the main route for processing chalcopyrite concentrates, although they are unfeasible for copper extraction from low-grade ores that make up the most copper reserves. Acid bioleaching is a promising technique for extracting copper from low-grade copper ores, and the technology has been studied for decades, but there is still no commercial-scale bioleaching application for copper recovery from chalcopyrite concentrates. Bioleaching is practiced with low-grade chalcopyrite ores in heap leaching processes with ores of multiple sulfide minerals. Research in this area has probed electrochemical reactions, biological activities, and interactions with microbes and mineral surfaces to integrate operational models for chalcopyrite bioleaching. The purpose of this chapter is to review the evolution in the understanding of the chemical leaching and bioleaching of chalcopyrite in the last 20 years, and the progress achieved so far.
Keywords: Chalcopyrite bioleaching; Electrochemical techniques; Galvanic interactions; Polarization; Redox potential control